The Pandemic, Financial Struggles, and Mental Health of Students - Patre, Smruti; Chakraborty, Debarun (Indian Journal of Finance, 2022)
The COVID-19 pandemic has left millions of people worldwide in financial distress. But it is the families and the children who are hit the hardest due to this worst economic crisis. Job losses and salary cuts were at their peak. In order to combat this situation, borrowings increased. This further deteriorated people’s lives, and they are yet to come out of it. Students at universities are one such tribe who have suffered the most due to COVID-19 induced public emergencies and lockdown tactics resulting in recurrent closures of educational facilities. Studies have confirmed that changes in their everyday learning environment, the blurring of their professional or career paths, the absence of meaningful relationships with others, and most importantly, the financial crisis faced by family — all had a substantial impact on their psychological well-being. The present study shed light on the academic, financial, and health struggles faced by university students. It also highlighted the role of various stakeholders in the ecosystem by proposing a model to combat these struggles.